THE LEGAL POLITICS OF THE GOVERNMENT ON THE ACQUISITION OF LAND FOR DEVELOPMENT IN TERMS OF THE ASPECTS OF THE IUS CONSTITUTUM AND IUS OPERATUM - Riadi Asra Rahmad (PENA LAW: International Journal of Law, 2022)
The policy of acquiring land for development by the government based on the ius constitutum of the aspect of assessing the amount of compensation, is carried out by means of an assessment of the value / price of the object of land acquisition by the land appraiser and / or public appraiser. Theimplementation of the government's policy towards the acquisition of land for development in the ius operatum phase is carried out through an agreement. The achievement of an agreement on land compensation between the parties in land acquisition will have an impact on the smooth running of the government in carrying out programs and policies in terms of development. So that the word agree is the key to opening the transfer of land rights status with deliberative techniques to reach consensus.